Psychological disposition to different types of coping to natural and social emergency states - Vicuña Peri, Luis Alberto (1999)
The present research compared on the basis of chronological age, civil state, gender and type of business the psychological aptitudes facing the emergency states with natural and social origin in 776 persons in Lima, whose sample of mistake size was 0,05, with a confidence level of 0,95. The informations about psychological aptitudes obtained through an ordinal scale. The data analyzed with the varianza´s analysis to ordinal data of one, two and three processes according to the intersections of variables. The variables above indicated not influence over psychological aptitudes and we can assert that people reactions are common as for the preservations as about life as physical integrity. The natural disasters such as earthquakes, tsunamis and fires generate more fear in population; the favorite place where they happen is the home. they consider a Civil Defence, The Red Cross and The Fire Brigade like help, but this doesn't reach to the affected, and damages reduce throught prevention. With respect to social damages such as Terrorism, Young Gangs and Assaults, they cause a lot of fear; and the reaction in front of those it is run towards an safe place, to alert and make the denounce.